Comparative study on the wind characteristics of tunnel–bridge and tunnel–flat ground infrastructures on high-speed railway. Issue 226 (July 2022) - Yang, Weichao; Liu, Yikang; Deng, E.; He, Xuhui; Lei, Mingfeng; Zou, Yunfeng
Abstract: The difference in natural wind characteristics of the tunnel–bridge (TB) and tunnel–flat ground (TF) infrastructure may result in varied aerodynamic behaviours of the high-speed railway train (HSRT). Hence, continuous natural wind sampling is conducted on typical TB and TF sites by using three ultrasonic and one three-cup anemometers. The mean and fluctuating wind characteristics of the two sites are compared and discussed in detail based on field measurement data. The main results can be concluded as follows: Firstly, the prevailing wind direction on the TB site is perpendicular to the running direction of the HSRT due to the occlusion effect, whereas the mean direction on the TF site is easily deflected by the near-ground vegetations and other obstacles. Secondly, the turbulence intensities of the TF site are larger than those of the TB site, and the lognormal distribution is applicable for describing the probability distribution of measured turbulence intensity on the two sites. Thirdly, the von Kármán spectrum accurately depicts the wind energy distribution of the TB and TF sites in the frequency domain, whereas the empirical spectrum adopted by the specification show inferior accuracy. Lastly, the coherence distance of the TB site is considerably longer than that of the TF site. The coherence distance of u and v components of the TB site is seven times longer than a train body (approximately 25 m), and that of u component of the TF site is shorter than two times of a train body. Highlights: Natural wind field of tunnel-bridge and tunnel-flat ground infrastructures are collected and analysed. Influence of terrain conditions on mean and fluctuating wind characteristics are compared and discussed. Accuracy of three empirical wind spectrum is compared and discussed. Coherence distance of the two sites is estimated and compared with the length of train body.